2017
DOI: 10.1542/peds.2017-0195
|View full text |Cite
|
Sign up to set email alerts
|

Methodological and Ethical Issues in Pediatric Medication Safety Research

Abstract: In May 2016, the Eshelman School of Pharmacy at The University of North Carolina at Chapel Hill convened the PharmSci conference to address the topic of "methodological and ethical issues in pediatric medication safety research." A multidisciplinary group of experts representing a diverse array of perspectives, including those of the US Food and Drug Administration, children's hospitals, and academia, identified important considerations for pediatric medication safety research and opportunities to advance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…A closer inspection reveals that most PGx research on SSA populations involves single gene–drug relationships; however, multigene–drug or gene panel testing provides a higher predictability of individual drug response. In addition, most studies have excluded pediatric populations, which is probably due to the existence of specific pediatric pharmacovigilance tools, including age-dependent drug dosage, relying on child-reported ADRs and the engagement of children and child care-givers in the research process [ 49 ]. The absence of clinical studies evaluating the economic value of implementing PGx testing in SSA health-care systems is also noteworthy, given that government and private insurers require evidence of the cost–utility of clinical tests for reimbursements.…”
Section: Paucity Of Clinical Pharmacogenetics Studies In Ssamentioning
confidence: 99%
“…A closer inspection reveals that most PGx research on SSA populations involves single gene–drug relationships; however, multigene–drug or gene panel testing provides a higher predictability of individual drug response. In addition, most studies have excluded pediatric populations, which is probably due to the existence of specific pediatric pharmacovigilance tools, including age-dependent drug dosage, relying on child-reported ADRs and the engagement of children and child care-givers in the research process [ 49 ]. The absence of clinical studies evaluating the economic value of implementing PGx testing in SSA health-care systems is also noteworthy, given that government and private insurers require evidence of the cost–utility of clinical tests for reimbursements.…”
Section: Paucity Of Clinical Pharmacogenetics Studies In Ssamentioning
confidence: 99%
“…Also, the propensity for pharmacokinetic differences between children and adults is well known. Pediatric medication safety research faces the difficulty of assessing child-reported adverse drug events ( 298 ).…”
Section: Considerations In Designing Future Clinical Trials For Neuromentioning
confidence: 99%
“…The physiological differences in pediatrics have not been fully characterized, which has made identifying safe and effective doses in this population a challenge 1 . In addition, the vulnerable nature of this population leads to limited sample size, and ethical barriers prevent pediatric research from being carried out 1,2 . As a result of lacking pediatric data, many medications are used off‐label in children with limited information on the optimal use 3 .…”
Section: Case Studymentioning
confidence: 99%